INFLUENCE OF THE TOTAL POWER OF THE HEART RATE VARIABILITY SPECTRUM ON THE SPECTRAL PARAMETERS DISTRIBUTION IN PATIENTS WITH ARTERIAL HYPERTENSION IN A PACED BREATHING TEST - Golubkina, E. O.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
To determine the effect of the total power (TP) of the heart rate variability (HRV) spectrum on the distribution of high, low and very low frequency waves, 40 patients with arterial hypertension (AH) at the age of 58 ± 9 years were divided into 5 groups according to the degree of TP decrease in the initial stage of the test: 1st – more than 3000 ms2; 2nd – 3000–2000 ms2; 3rd – 2000-1000 ms2; 4th – 1000–500 ms2; 5th – less than 500 ms2. To assess HRV parameters in each group, 3 stages of the paced breathing test with a double (light and sound) metronome were evaluated; the hardware and software complex «Cardiolab» («HAI-Medica») was used. The distribution of the parameters was estimated taking into account the median, 25 and 75 quartiles. To estimate the differences between the statistical samples, the nonparametric Mann-Whitney U-test was used, as well as the Craskell–Wallis criterion. Statistically significant differences were considered between the data at a value of p < 0.05. It was found that the greater is the degree of TP reduction, the more significant is the autonomic imbalance, as well as the decrease in the influence of paced breathing on the regulation of the heart rhythm; at TP values below 1000 ms2 not only the parasympathetic component decrease is observed, but also the transition from sympathicotonia to the neurohumoral factors prevalence. In patients with arterial hypertension, there is a tendency of decrease in the total power of the HRV spectrum, thus reflecting the decreased functional capacity of heart rhythm regulation.The lower the degree of TP, the more significant is the disturbance of HRV regulation with a decrease in the parasympathetic component of the heart rate variability spectrum and the dominant influence of sympathetic and neurohumoral factors.The influence of the paced breathing on the heart rhythm regulation falls depending on the decrease in the total power of the HRV spectrum: at TP values below 1000 ms2 not only the parasympathetic component decrease is observed, but also the transition from sympathotonia to the neurohumoral factors prevalence.Decrease in TP can be considered as an indicator of aggravation of autonomic and neurohumoral regulation.Thepaced breathing test allows determine the basic level of cardiac activity regulation and dynamic disruptions in the distribution of HRV components in the metronomized breathing, as well as the possibilities for restoring the regulatory balance of heart rate variability, which is especially important in the examination of patients with arterial hypertension.